Prevalence, comorbidities, and disease-related complications of rheumatoid arthritis in Colombia: a national cross-sectional study based on administrative claims data - Kevin Maldonado-Cañón; Giancarlo Buitrago; Gerardo Quintana-López (Advances in Rheumatology)
Abstract Background To date, there has been limited exploration, particularly on a national scale, of the prevalence patterns of comorbidities and complications associated with rheumatoid arthritis (RA) in Colombia. We aimed to analyze the prevalence patterns of comorbidities and disease-related complications of RA patients enrolled in Colombia’s contributory healthcare regime. Methods We performed a nationwide observational descriptive cross-sectional study using administrative claims data. We used a set of sensitive and specific electronic algorithms (i.e., a set of rules) applied to linked data based on ICD-10 codes and unique medication use codes. We compared all those algorithms with several sources, including governmental agencies and scientific literature, to identify all the known adults treated for RA. Results A total of 123,080 RA cases for 2018 were identified, corresponding to a point prevalence of 0.86 (95% CI 0.86–0.87) per 100. Compared to a non-RA reference population, hypertension (68.2 vs. 20.0%), osteoarthritis (43.6 vs. 6.1%), and osteoporosis (18.6 vs. 1.1%) provided larger standardized mean differences. Lupus (30.04; 95%CI 29.3–30.8), multiple sclerosis (7.18; 95%CI 6.6–7.8), and osteoporosis (5.57; 95%CI 5.5–5.6) provided higher age- and sex-adjusted prevalence ratios. Disease-related complications were found in 62.2% of cases. Conclusions We describe the first comprehensive assessment of the prevalence patterns of disease-related complications and comorbidities that define the RA burden of disease within a multimorbidity profile. Also, our study provides a narrower and more reliable point prevalence estimate for RA in Colombia.